Penguatan Kapasitas Kelompok Usaha Sijati dalam Pengelolaan Budidaya Jamur Tiram di Desa Sait Buttu Saribu - Rangga Restu Prayogo; Hendra Saputra; Hidir Efendi; Khafi Puddin; Fadli Agus Triansyah; Safitri Maya Sari; Annisa Az Zahra; Dimas Very Prabowo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was implemented to strengthen the capacity of the SIJATI Business Group in managing oyster mushroom cultivation in Sait Buttu Saribu Village, Simalungun Regency. This activity was motivated by the group's great potential in oyster mushroom production, but still faces obstacles in production, marketing, and business management aspects. The method used was a participatory-collaborative approach through stages of socialization, training, mentoring, provision of modern production equipment, strengthening digital marketing, and business management coaching. The results of the activity showed a significant increase in the group's capacity. From a production aspect, the use of a stainless steel steamer machine and modern baglog racks increased time efficiency, saved energy, and doubled production capacity. From a marketing aspect, digital marketing training and collaboration with students as resellers expanded market reach, increased consumer interaction, and drove increased turnover. From a management aspect, digital-based financial records and assistance with business legality strengthened institutions and opened opportunities for access to capital. This program also had a social impact by increasing the economic contribution of housewives who were members of the group, thereby contributing to the welfare of the village community. Overall, strengthening the capacity of the SIJATI group aligns with achieving the Sustainable Development Goals (SDGs), particularly in poverty alleviation, gender equality, and inclusive economic growth. Therefore, this activity can serve as a model for empowering competitive and sustainable local commodity-based MSMEs.